A New Compact CPW-Fed Dual-Band Uniplanar Antenna for RFID Applications - Ahmed El Hamraoui; El Hassane Abdelmounim; Jamal Zbitou; Laarbi Elabdellaoui; Hamid Bennis; Mohamed Latrach (Universitas Ahmad Dahlan, 2018)
In this paper a new dual-band uniplanar monopole antenna fed by Coplanar Waveguide (CPW) line is proposed for Radio Frequency Identification (RFID) applications. The antenna structure includes a CPW fed line and the dual-band operation is achieved from the G-shaped folded antenna. The antenna parameters have been investigated and optimized by using CST Microwave Studio. To validate the CST Microwave Studio results before the antenna achievement, we have conducted another study by using ADS. The final circuit was achieved, measured and validated. Experimental results show that the proposed antenna with compact size of 30*45 mm2 is simple in design and compact in size. It exhibits broadband impedance matching, consistent omnidirectional radiation patterns and appropriate gain characteristics suitable for the microwave RFID applicartions.